Controversial Topics and Their Didactic Use: Analysis of the Activities Included in Italian and Spanish Textbooks - Ferreras-Listán, Mario; Pineda-Alfonso, José Antonio; Hunt-Gómez, Coral Ivy; Baisotti, Pablo (Pedagogika, 2020)
This paper explores the didactic treatment of Franco’s dictatorship and Mussolini’s Fascism in History textbooks at a Secondary Education level. Using a mixed methodology, 278 activities were analysed and a typology was established. Despite that, the studied literature clearly advocates for the use of controversial topics due to their high educational potential, results show that controversial topics are avoided in the analysed textbooks, as they provide teachers an „aseptic recipe“ to deal with them.